Are You Ready To Embrace New Technology? Accounting Practitioners In Malaysia - Azleen Ilias; Nasrudin Bin Baidi; Rahida Abd. Rahman (2020)
The objective of this study is to investigate the readiness (optimism, innovativeness, discomfort, insecurity and overall Technology Readiness Index) among accounting practitioners in Malaysia. Specifically, this study has identified accounting practitioners’ intention to adopt any type of new technology. In addition, this study has examined the difference in technology readiness among gender, age, level of education and profession. This study employed a questionnaire survey to gather 518 accounting practitioners from a different profession in Malaysia (Kuala Lumpur, Putrajaya, Selangor). In relation to readiness, accounting practitioners also seem to be optimistic in knowing any new technology. With regard to the Technology Readiness Index (TRI) factors, there are no significant differences among accounting practitioners across gender. But there are significant differences with regards to the accounting practitioners' age, level of education and profession on optimism, insecurity and partial difference for overall readiness. Thus, demographic characteristics could also impact TRI factors. Further study should consider specific technology and profession to examine the real issue regarding the technology acceptance within an accounting perspective.